Access determinants and use of health services among the elderly (Bioscience Journal, 2017)
this study aimed to describe the characteristics related to access to and use of health services, and verify factors associated with the use of services among the elderly. This is a cross-sectional analytical study conducted with 705 urban elderly in Uberaba/Minas Gerais. Were used: structured instrument related to socioeconomic data, Katz, Lawton and Brody scales and Fried Fragility Phenotype; and questionnaire from the National Survey by Domicile Sample for access and use of health services. The procedure was the descriptive and logistic regression analysis (p